Kemunculan Lingua Sacra dalam Sejarah al-Qurâ€™an (Perspektif John Wansbrough) - Musaddad, Asep (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2016)
The language of the Qurâ€™an has long been disputed in the history of Qurâ€™anic exegesis. It particularly related to the discourse of Arabic rhetoric and in turn has also sparked a considerable controversy especially in the context of â€œkalamâ€ sectarianism (madhhab kala>mi>). John Wansbrough, a famous Western scholar, is one of those who paid much attention on the issue in his monumental work, Qurâ€™anic Studies. The work is regarded as one of the exponents of the â€œhistorical-criticalâ€ study of the Quran that contains several key issues, including the intersection of the Qurâ€™an with Arabic rhetoric discourse, which in turn is also responsible for the emergence of sacred sense in the two domains. Starting with Wansbroughâ€™s key issues on Qurâ€™anic Studies, this article provides a brief introduction to his thought about the emergence of the concept of the sacred language (lingua sacra) in the history of the Qurâ€™an and some of the implications thereof.Keywords: John Wansbrough, lingua sacra, rhetorical exegesis, majaz.